Anesthetic Management of Laparoscopic Surgery on a Pediatric Patient: Case Report - Handoko, Adelia; Gemawan, Taufiq; Lubis, Arinie Awindya (Jember Medical Journal, 2024)
Inguinal hernia is an opening on myofascial oblique muscle and transversal muscle or the failure of Nuck canal or processus vaginalis during the gestation week which allows herniation of intra-abdominal or extraperitoneal organ. A 5-year-old child was diagnosed with a left lateral inguinal hernia. The results of the inguinal ultrasound showed movement and movement of the intestines in the left inguinal area through a defect measuring approximately 2.96 centimeters. The patient was planned to undergo laparoscopic high ligation hernia. Laparoscopic technique in adult commonly applied with special consideration. However, the practice in pediatric patient could be more challenging for anesthesiologist. Although laparoscopic surgery is less invasive it could cause more stress due to the pressure of the intra-abdominal pneumoperitoneum by CO2 that is done during the procedure, which then causes hypercapnea due to the absorption of CO2, the decrease of tidal volume, and the decrease of end-tidal volume. Considering pediatric’s different physiology compared to adult and the risks of laparoscopic surgery, special anesthesia management should be conducted.